Editorial: “Are Technology Acceptance Models still fit for purpose?” - O'Dea, Michael (Journal of University Teaching and Learning Practice, 2025)
Technology acceptance research has been an important and fruitful research domain since the late 1980s. At the forefront has been the Technology Acceptance Model (TAM) and related models such as UTAUT. These models aim to explain and predict adoption of technology, so that adoption can be improved and decisions can be made regarding technology implementation. The predictor variables of adoption are Behavioural Intention (BI) and Actual Use (USE). The TAM defines two key determinants of BI, Perceived Ease of Use (PEOU, sometimes also abbreviated as PEU) and Perceived Usefulness (PU). Technology Acceptance Model based research has been applied to many different technologies, in different fields of use, in different cultural contexts and at different scales, globally and whilst being robust, the approach does have limitations. These call into question, to greater and lesser degrees, the validity of the findings and/or the usefulness of the model under certain contexts. This issue examines the debates surrounding these limitations under the umbrella question of “TAMs are they still fit for purpose?” The commentary article and book reviewed directly address these debates and the articles demonstrate how researchers are responding to the debates, exploring them in different contexts, at different scales and for different technologies. The editorial concludes by proposing future directions for the field to continue its evolution and remain as an effective and important tool in the understanding technology adoption in an age of frequent and rapid technological innovation in education.